A case of paediatric spotted fever presenting with acute hepatitis and encephalopathy - Singh, Jatinder; Amandeep,; Dubey, Arnav (International Journal of Contemporary Pediatrics, 2026)
Rickettsial infections caused by the spotted fever group Rickettsia remain an underrecognized cause of acute febrile illness in children, particularly in endemic regions. Although fever and rash constitute the classical presentation, atypical organ involvement may occur, leading to diagnostic delay. We report a rare presentation of pediatric spotted fever complicated by acute hepatitis and encephalopathy in a child from a rural agricultural background. The child initially presented with fever, anorexia, and malaise, followed by jaundice and altered sensorium. Extensive evaluation excluded common viral, bacterial, and parasitic etiologies. Serological testing supported the diagnosis of spotted fever, and prompt initiation of doxycycline resulted in rapid clinical and biochemical improvement. This case emphasizes the importance of maintaining a high index of suspicion for rickettsial infections in children presenting with unexplained hepatic and neurological involvement, even in the absence of rash or eschar. A child from a rural area developed an uncommon form of spotted fever affecting the liver and brain. Early recognition and treatment with doxycycline led to complete recovery, highlighting the need to consider rickettsial infections even when classical symptoms are absent.